Pelatihan Pelaporan Keuangan Sederhana bagi UMKM Pemula - Amin Wijoyo; Stewart Sebastian; Brayden Brayden; Eric Bryan Lie (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy; however, most early-stage MSME owners still face significant limitations in managing their business finances. The main challenges include a lack of understanding regarding financial recordkeeping, the absence of separation between personal and business finances, and limited knowledge of financial reporting standards based on SAK EMKM. This community service activity aimed to improve the understanding and skills of early-stage MSME owners in preparing simple financial reports. The training was conducted in a face-to-face format at the Integrated Business Service Center (PLUT) – KUMKM of Belitung Regency on May 21, 2026, using a combination of material presentation, contextual practice problems, and group discussion sessions. The results indicated that approximately 80% of participants demonstrated a solid understanding of the material and showed improved ability to read, prepare, and analyze simple financial statements. Participants also exhibited high enthusiasm and expressed interest in exploring accounting topics further. This activity is expected to encourage MSME owners to develop disciplined financial recordkeeping habits, enabling them to manage their businesses more professionally and sustainably.